Nursing Intervention in adolescence: an institution experience in Public Secondary School - Martínez Esquivel, Daniel (2013)
Adolescence is a key stage of life to the empowerment that must have health, but it has many needs that healthteams still have not resolved. This article presents an analysis of the health situation of a group of teenagersattending a public institution of higher education and intervention by nursing students, focused on creatingconditions for health promotion and disease prevention. This research was conducted from a quantitative,descriptive and was performed in an institution of secondary education in the period from September toNovember 2012. We worked with students and students of eighth and ninth year with a convenience sample. Themain results indicated needs in sexuality, healthy lifestyles and conflict resolution. To address these issuesevolved different strategies planned, organized, directed and controlled by the individual. We conclude that healtheducation in adolescents is a public health problem and that nurses must meet.